2010
DOI: 10.1021/bc9003052
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Porous Protein Crystals in Development of Biohybrid Materials

Abstract: Protein assemblies have attracted increasing attention for construction of biohybrid materials. Protein crystals can also be regarded as solid protein assemblies. The present work demonstrates that protein crystals can be employed as porous biomaterials by site-specific modifications of the crystals of recombinant sperm whale myoglobin mutants. The myoglobin crystals of space group P6 provide hexagonal pores consisting of the building blocks of six Mb molecules, which form a pore with a diameter of 40 A. On th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 34 publications
0
34
0
Order By: Relevance
“…These crystals are able to capture and deposit metal ions and metal complexes within solvent channels when the crystals are soaked in the solutions containing the metal ions because the amino acid side chains responsible for coordinating the metal ions are periodically aligned on the surface of solvent channels of the crystal lattices 17–22. We have demonstrated the accumulation of functional molecules such as metal complexes and metal clusters into the solvent channels of porous myoglobin crystals by chemical conjugation and coordination interactions 23, 24. With respect to inorganic materials, it has been reported that protein crystals can serve as nanoreactors for the preparation of nanoparticles 25, 26.…”
Section: Characteristics Of the Copt‐nps Prepared In The Hewl Crystalmentioning
confidence: 98%
“…These crystals are able to capture and deposit metal ions and metal complexes within solvent channels when the crystals are soaked in the solutions containing the metal ions because the amino acid side chains responsible for coordinating the metal ions are periodically aligned on the surface of solvent channels of the crystal lattices 17–22. We have demonstrated the accumulation of functional molecules such as metal complexes and metal clusters into the solvent channels of porous myoglobin crystals by chemical conjugation and coordination interactions 23, 24. With respect to inorganic materials, it has been reported that protein crystals can serve as nanoreactors for the preparation of nanoparticles 25, 26.…”
Section: Characteristics Of the Copt‐nps Prepared In The Hewl Crystalmentioning
confidence: 98%
“…Methyl viologen (MV) mediated the electron transfer between Zn porphyrin (ZnP, electron donor) and an oxo‐centered triruthenium cluster (Ru 3 O), electron acceptor) in the crystal. Remarkably, the Mb crystals form a channel structure with a diameter of 2–4 nm, which provides enough space for the accumulation of the functionalizing compounds . The applied crystal soaking method enabled the site‐specific fixation of Ru 3 O and the anisotropic diffusion of MV.…”
Section: Chemoenzymatic Cascade Reactionsmentioning
confidence: 99%
“…The Mb crystals with space group P6 form several channel structures (diameter 2-4 nm), which provide enough space for accumulation of nanosized functional molecules as previously reported. [24] The Mb crystal spaces are available for site-specific fixation of Ru 3 O and anisotropic diffusion of MV. Moreover, fixation of zinc porphyrin units with a light-harvesting function in the Mb crystal is achieved by crystallization of zinc porphyrin substituted myoglobin (ZnMb).…”
mentioning
confidence: 99%